Application of Low-Intensity Laser in the Treatment of Skeletal Muscle Injury in Runners - Youdong Chen; Qiang Li (Emergency Medicine International)
With the continuous improvement of people’s economic level, running, as the most common sports, is not limited by sports venues and sports levels and deeply loved by people. However, during running, soft tissue resonates with the impact force, increasing the load on joints and tendons and potentially leading to sports injuries. The purpose of this article is to study the application of low-intensity laser in the treatment of muscle strain. This article analyzes running, muscle adjustment, and lower limb stiffness. On the basis of theory, 20 healthy male college students were selected as research objects in the experimental part. The subjects were allowed to run at three speeds: slow, medium, and fast. The kinematics, dynamics, and surface EMG signals of the subjects during running were collected to analyze the effect of low-intensity laser therapy on exercise muscle strain. The experimental results showed that a low-intensity laser can effectively alleviate muscle inflammation, reduce the number of cell damage, bring the mean and integral optical density of protein to the normal level significantly, and reduce the strain degree of exercise muscle. In this article, a statistical method was used to obtain the gait cycle time (P & LT; 0.01) and support cycle time (slow P<0.01).